THE CONCEPT OF “SOFT POWER” IN INTERNATIONAL RELATIONS (USING SAUDI ARABIA AS AN EXAMPLE) (The Journal of Interdisciplinary Human Studies, 2026)
The article scientifically analyzes the concept of “soft power” based on Joseph S. Nye Jr. theory and substantiates its difference from traditional power concepts. Also, a comparative analysis is carried out with the realistic approach of Hans J. Morgenthau and Kenneth N. Waltz. The study examines the mechanisms of international influence through culture, religious factors, and media diplomacy using the example of Saudi Arabia. As a result, it is scientifically concluded that “soft power” is an important theoretical and practical tool for increasing the authority of states in the international arena.
Keywords: Soft power; Saudi Arabia; Joseph Nye; constructivism; public diplomacy; media diplomacy